Regulation and cloning of the gene encoding amylase activity of the ruminal bacterium Streptococcus bovis. - Cotta, M A (1993)
Streptococcus bovis is an important starch-degrading ruminal bacterium that has been implicated as being important in the etiology of a number of ruminal pathologies associated with diets high in grains. Previous studies with S. bovis have shown that amylase production was influenced by the growth substrate, but the nature of this regulation was not determined. The current study was conducted to better describe the regulatory phenomena and gain a better understanding of the molecular characteristics of this activity. Nutritional experiments demonstrated that the presence of starch or the starch-derived disaccharide maltose was required for maximum amylase production. Subsequent time-course experiments showed that amylase synthesis was induced by maltose and repressed by glucose, cellobiose, and fructose, while inulin and lactose had little effect on enzyme accumulation. The effects of the added antibiotics rifampin and tetracycline were consistent with transcriptional control of amylase synthesis. Analysis of S. bovis cells grown on glucose or maltose showed that they contained similar low levels of cyclic AMP, indicating that it was unlikely that regulation of amylase synthesis was mediated through a mechanism involving this nucleotide. The amylase gene from S. bovis JB1 was cloned and expressed in Escherichia coli. The amylase produced in E. coli was of lower molecular weight than that synthesized by S. bovis and had catalytic characteristics different from those of S. bovis amylase. When the gene was introduced back into S. bovis JB1, only one form of amylase activity was detected, indicating that the entire gene was present on this insert. The use of the amylase gene as a genetic probe for identification of S. bovis strains is discussed.